Assessing the needs of the families of persons affected by Acquired Brain Injury with the Family Needs Questionnaire - López de Arroyabe-Castillo, Elena; Calvete, Esther (Anales de Psicología / Annals of Psychology, 2012)
The present study aimed to adapt the Family Needs Questionnaire (FNQ; Kreutzer, 1988) to the Spanish population. This instrument was developed to assess perceptions of the families of their own needs after Acquired Brain Injury (ABI) of a relative. The questionnaire includes 6 factors: Need for Health Information, Need for Emotional Support, Need for Instrumental Support, Need for Professional Support, Need for a Support Network and Need for Involvement with Care. 223 family members of persons with ABI participated in this study. Factor analysis confirmed the original 6 factor structure and internal consistency coefficients were good. The results also show that information needs are considered as the most important and satisfied. In contrast, the needs of professional and emotional support are the least satisfied.